Extending the interval between second vaccination and slaughter: I. Effects on growth, scrotal size and stress responses of immunocastrated ram lambs. (18th January 2019) - Needham, T.; Lambrechts, H.; Hoffman, L. C.
Abstract : Immunocastration provides a less invasive means of castrating lambs. Considering increasing consumer awareness, the efficacy of this technique on commercial slaughter lambs needs to be further investigated and its effects on growth and stress responses need to be established. This study compared the growth rate, testes size and stress responses of immunocastrated lambs with that of lambs physically castrated with a Burdizzo clamp, as well as intact rams. A total of 40 Dohne Merino ram lambs (average live weight = 45.4±3.68 kg) were randomly allocated to the following four treatment groups: control (intact; R), Burdizzo-castrated (on day 2; B), immunocastrated with a 4-week (ICS4), or a 6-week (ICS6) interval between the second immunocastration vaccination and slaughter. Within the immunocastration treatments, the reaction to vaccination was assessed through injection site scoring, recording the local injection site surface temperature and assigning a walking score. The response to Burdizzo castration was assessed by scoring the reaction during the procedure, testes palpation reaction, walking gait and measuring testis temperature. Additional parameters recorded included BW, serum cortisol concentration, scrotal circumference and rectal temperature. Pain behaviours were described for the short-, medium- and long-term effects after the two methods of castration. Predominantly, tissue-hardening and bruising occurred at the injection sites of immunocastrates, but little effect was observed on walking comfort and no effect on injection site temperature or rectal temperatures. After Burdizzo castration, lambs spent more time in abnormal postures, and from day 3 (D3) to D8 of the trial, discomfort was observed during testes palpation and walking in B lambs. Serum cortisol concentrations were elevated in B lambs on D3 and D15, indicating physiological stress. Thus, immunocastration improved the welfare of castrated lambs as assessed by cortisol secretion, scrotal swelling and pain behaviours, without influencing growth rate.